ANALISIS EFEKTIVITAS PEMANFAATAN KREDIT MODAL KERJA USAHA KECIL DAN MENENGAH (UKM) PADA KOPERASI SIMPAN PNJAM (KSP) ADIL MAKMUR PONTIANAK - B21108006, Masrita Pasaribu (Jurnal Pembangunan dan Pemerataan, 2014)
This thesis entitled â€œ Analysis effective use of working capital loans to the Credit Unions (KSP) PROSPEROUS PONTIANAK FAIRâ€. The purpose of this study was to determine and analyze the effectiveness of utilization of working capital loans to micro credit business credit cooperatives (KSP) Prosperous Justice Pontianak. The methodology used in the study is qualitative descriptive through primary date from cooperative members KSP Prosperous Justice Pontianak then analized according to the research objectives. Based on the analysis of the utilization of working capital loans efectivitas Micro Credit Enterprises On Credit Unions (KSP) Prosperous Justice Pontianak it can be concluded that Proceeds from sales and business profits obtained showed no difference in the average before and after obtaining a business loan. This Indicates that the working capital loan assistance provided by the cooperative Saving and Loans (KSP) Prosperous Justice Pontianak is Rp.2.000.000,-. Not effective role in supporting the development of micro credit business, credit assistance is still small compared to the price increase. Â  Keywords : Effectiveness, Utilization of Working Capital Loans, Small Business and micro